2022
DOI: 10.1039/d2cc01901a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical selenium–π–acid promoted hydration of alkynyl phosphonates

Abstract: An unprecedented electrochemical selenium-π-acid promoted hydration of internal alkyne assisted via phosphonates was described. Thus, valuable (hetro)aryl and alkyl ketones could be accessed under mild, metal- and external oxidant-free conditions....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In 2022, Mei proposed an elegant regioselective β-hydration of alkynyl phosphonates 73 via electrochemical oxidative organoselenium catalysis (Scheme 42). 84 The authors showed that the combination of organic electrosynthesis and selenium catalysis (PhSeSePh) promoted an electrophilic PhSe + cationic species. A plausible mechanism involving the assistance of the phosphonate group was proposed by the authors and was supported by H/D exchange, the 18 O label, and radical scavenger experiments.…”
Section: β-Hydration Of Alkynesmentioning
confidence: 99%
“…In 2022, Mei proposed an elegant regioselective β-hydration of alkynyl phosphonates 73 via electrochemical oxidative organoselenium catalysis (Scheme 42). 84 The authors showed that the combination of organic electrosynthesis and selenium catalysis (PhSeSePh) promoted an electrophilic PhSe + cationic species. A plausible mechanism involving the assistance of the phosphonate group was proposed by the authors and was supported by H/D exchange, the 18 O label, and radical scavenger experiments.…”
Section: β-Hydration Of Alkynesmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information [14,24,28,33,37,40–62] …”
Section: Figurementioning
confidence: 99%
“…In 2022, Mei’s group developed an efficient phosphonate-assisted hydration of internal alkynes 9 via electro-catalysis with a PhSeSePh mediator (Scheme 3 ). 9 Employing room temperature conditions, utilizing RVC as the anode, platinum plate as the cathode, CH 3 CN as the solvent, Et 4 NBF 4 as the electrolyte, and a constant current of 10 mA, the reaction, catalyzed by 0.5 equivalent of PhSeSePh, proceeded between acetylenes and phosphonic acid groups to furnish a series of (heterogeneous) aryl and alkyl ketone compounds 10 . This protocol showcases remarkable chemo-/regioselectivity and scalability with internal alkynes harboring diverse functional groups, enabling facile access to a broad spectrum of (hetero) aryl and alkyl ketones with high efficiency.…”
Section: Electrochemical Selenium-catalyzed Reactionsmentioning
confidence: 99%